The Effect of Three-Dimensional Learning Media on Elementary School Students’ Learning Outcomes in the Cube Topic: Pengaruh Media Pembelajaran Tiga Dimensi pada Materi Kubus terhadap Hasil Belajar Siswa Sekolah Dasar - Moch. Fauzi; Fatriatul Lailatul Jannah (ELRISPESWIL - Lembaga Riset dan Pengembangan Sumberdaya Wilayah, 2026)
This study examined whether learning with three-dimensional (3D) concrete media is associated with improved mathematics learning outcomes on the cube topic among fourth-grade students. The study employed a quantitative approach with a one-group pretest–posttest design. The participants were 26 fourth-grade students from SD Negeri Randuagung 01, Lumajang Regency, East Java, selected purposively based on relevance to the research objective. The intervention used a low-cost 3D cube media package consisting of a transparent acrylic cube model with colored faces, a wire-frame cube, and 1 cm³ unit cubes to support exploration of cube elements and volume concepts. Data were collected using a 20-item multiple-choice test (content validity via expert judgement; Cronbach’s alpha = 0.82), classroom observation, and documentation. Data analysis included the Shapiro–Wilk normality test, paired-samples t-test, and N-gain analysis. Results showed that both pretest and posttest data were normally distributed (p > 0.05). The paired-samples t-test showed a statistically significant increase in posttest scores (p < 0.001), indicating that students performed better after learning with 3D media. The average N-gain was 0.61 (61.45%), which falls into the “moderate” improvement category. These findings suggest that in this context, learning supported by 3D concrete media is associated with meaningful improvement in students’ understanding of cube concepts. Future studies are recommended to include a control group and larger samples to strengthen causal inference and generalizability, particularly in under-resourced school contexts using a clearly specified 3D media package.